GENESIS 1:1-3 AND ITS MAIN EVANGELICAL THEORIES OF INTERPRETATION - Antonio Batista Santos, Elias (Revista Areia, 2023)
The present text aims to reflexively analyze the two opening verses of the first book of the Jewish/Christian Old Testament, Genesis, taking into account its context and scrutinizing the evangelical theories developed around them, in order to understand which of these it is more coherent. To this end, a qualitative approach was used, through documental analysis of the pericope mentioned above, as well as a literature review with works that deal with the theme. Thus, initially, general questions were raised about the book of Genesis, in order to have a basis for the following steps; after that, the main theories about Genesis 1:1-3 were sought; it then followed with an analysis of the chosen pericope, that is, Genesis 1:1-2, confronting the theories previously raised with the discoveries made. It was observed that verse 1 refers to a first divine action, verse 2 being the description of its state. In this sense, it was seen that the expression “without form and void”, in fact, wants to convey the idea of ​​something inappropriate for human life and, consequently, without it. It is concluded that the theory that most coherently behaves with the biblical text, from an evangelical perspective, is that of “initial chaos”, although the idea of ​​“chaos” is not so familiar to the pericope.